Investigation of wet etching technique for selective patterning of ferroelectric zirconium-doped hafnium oxide thin films for high-frequency electronic applications - Livia Alexandra Dinu; Cosmin Romanitan; Martino Aldrigo; Catalin Parvulescu; Florin Nastase; Silviu Vulpe; Raluca Gavrila; Pericle Varasteanu; Andreea Bianca Serban; Rihem Noumi; Olga M. Ishchenko (Materials & Design, 2023)
This paper presents the area-selective wet etching (ASWE) method as a novel approach to have a selective patterning of a 6.8 nm-thick zirconium-doped hafnium oxide (HZO) thin film, to improve the performance of a metal ferroelectric metal (MFM)-like structure. According to the electromagnetic simulations of microwave phase shifters with patterned HZO thin films, it is underlined the importance to have selectively targeted areas covered with HZO instead of full-coverage wafers, to gain a further increase in the microwave performance of low-voltage tunable high-frequency components. The impact of the ASWE method on the morpho-structural properties was studied using various investigation tools in a non-destructive manner. X-ray reflectivity (XRR) has been employed at different immersion times, up to 120 s. Based on the extended Fast Fourier Transform (FFT) analysis, as well as from the simulation of the experimental curves in the framework of parallel-tempering algorithm, the determination of the etching rate became possible. X-ray diffraction (XRD), atomic force microscopy (AFM), and X-ray photoelectron spectroscopy (XPS) clearly indicated the complete removal of HZO after etching processes at 180 s. The method is fast, reliable, and low-cost, thus filling the actual gap in providing the necessary ferroelectric thin films exclusively in selected areas of interest.